Professional independence of students - the future teachers of an artwork in works of known teachers of the past - V.V. Buchkivska (Освітній вимір, 2006)
In clauses {articles) the problem of professional independence of students - the future teachers of an artwork in works of known teachers is examined: V. Suhomlinskogo, V. Kozakova, A. Makarenko, V. Bezpalka and others.